Inhibitory Effects of Dexamethasone on Hepatocyte Growth Factor-Induced DNA Synthesis and Proliferation in Primary Cultures of Adult Rat Hepatocytes - Mitsutoshi Kimura; Hajime Moteki; Masahiko Ogihara (Elsevier, 2011)
We investigated the effects of dexamethasone on hepatocyte growth factor (HGF)-induced DNA synthesis and proliferation in serum-free primary cultures of adult rat hepatocytes. Isolated hepatocytes were cultured at a density of 3.3 × 104 cells/cm2 in Williams' medium E containing 5% newborn bovine serum and various concentrations of dexamethasone for 1, 2, and 3 h. After a 3-h attachment period, the medium was then changed, and cells were cultured in serumfree dexamethasone (10−10 M)-containing Williams' medium E with or without glucocorticoid receptor antagonists. After addition of dexamethasone to the culture medium, the growth-stimulating effects of HGF (5 ng/mL) on the primary cultured hepatocytes were time- and dose-dependently inhibited. The mineralcorticoid aldosterone (10−7 M) did not produce the same growth-inhibitory effects as dexamethasone (10−8 M). The inhibitory effects of dexamethasone were reversed by treatment with the glucocorticoid-receptor antagonist mifepristone (RU486, 10−6 M) or a monoclonal antibody against glucocorticoid receptor (100 ng/mL). In addition, the growth-inhibitory dose of dexamethasone did not affect HGF-induced receptor tyrosine kinase and extracellular signal-regulated kinase 2 phosphorylation. These results indicate that dexamethasone dose-dependently delays and inhibits HGF-induced DNA synthesis and proliferation through its own intracellular receptor in primary cultures of adult rat hepatocytes. Keywords:: DNA synthesis, proliferation (cultured hepatocyte), hepatocyte growth factor, dexamethasone, signal transduction